PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII MTsN TARUSAN KABUPATEN PESISIR SELATAN - Yanti Nazmai Ekaputri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
This research was conducted due to the students’ mathematics communication ability in class VIII of MTsN Tarusan was still low. This problem could be seen from the result of observation done to the students and interview done to mathematics teachers in MTsN Tarusan. To overcome the problem, generative learning model was applied. The purpose of this research was to reveal the effect of using generative learning model on the students’ mathematics communication ability. This was a quasi experimental research. The data collected was analyzed by using t-test, t’ test and Mann Whitney U test. Based on the result of data analysis, it was figured outthat mathematics communication ability of the students taught by using generative learning model was better than that of students taught by using conventional learning.